Karakteristik dan Motivasi Wisata Sebagai Arahan Konsep pengembangan Atraksi di Pantai Somandeng Kabupaten Gunungkidul - , ISNIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The tourism sector is one sector of the biggest foreign exchange contributors of a country. The tourism sector in Indonesia is developing rapidly. One of many attractions in Indonesia, which have begun to develop, is Somandeng Beach. The beach has become one of the natural attractions in Gunungkidul, Yogyakarta. Since the beginning of the opening, this beach is a tourist destination and has started to be visited by tourists, thus it encourage the government to provide the best service to travelers, by establishing and implementing policies to increase tourist arrivals. In tourist traveling to a destination, tourists have certain motivations that make them to choose to visit tourist destinations. Similarly, tourists visiting the beach Somandeng have a certain motivation. The purpose of this research is to know the characteristic & motivation of tourist is Somandeng Beach. The method which is used in this research is combination method or mixed method which is combined quantitative & qualitative method chronologically. Quantitative method used to pick the sample as a base to determine respondent amount, and afterwards used qualitative descriptivemethod to explain the founding data so that it can be understandable. This researchwas conducted by collecting primary data with quistionnaires & secondary data from literature. Based on these results, it indicates that the results of the analysis of the characteristics and motivations, tourists who visit Somandeng Beach come from outside DIY and are mostly male, dominated by young age, with last education background high school & and has self-employed jobs that come in group and their motivation to visit Beach Somandeng is dominated by physical motivation.